In vitro PROPAGATION OF Heliconia curtispatha P, PLANT USED AGAINST SNAKEBITE BY SOME RURAL COMMUNITIES OF THE COLOMBIAN REGION OF URABÁ - ALARCÓN P., Juan C.; MARTINEZ M., Diego M.; SALAZAR-OSPINA, Andra (Vitae, 2011)
Heliconia curtispatha Petersen (Zingiberales) commonly known as platanillo, is used in colombian traditional medicine by its anti-edema, antihaemorrhagic and neutralising action of Bothrops asper (mapaná, X) venom, responsible for 95% of snakebites in the country. The previous, emphasizes its utility and potential function as helper in the treatment of the ophidian accident. The in vitro propagation techniques becomes an interesting tool for plant and metabolites production, because of the hazardous accessibility to plants in their natural environment and the deficiency of previous studies on in vitro multiplication of the specie. In the present work, plantlets are obtained from seeds and its in vitro p ropagation is evaluated in Murashige & Skoog semi-solid and liquid medium without or in combination with citokinines-like. Experimentally, it promotes the propagation of Heliconia (2 weeks outbreaks -1) when using Murashige & Skoog liquid medium without added growth regulators or by using Murashige & Skoog semisolid adding 2 mg.L-1 6-benzylaminopurine 0.93 week outbreaks -1. This is the first report of in vitro propagation of H. curtispatha and the first step for the study of secondary metabolites with potential venom that can occur under such conditions.